Four weeks of optimal load ballistic resistance training at the end of the season attenuates declining jump performance of women volleyball players - Newton, R. U.; Rogers, R. A.; Volek, J. S.; Häkkinen, K.; Kraemer, W. J. (The Journal of Strength and Conditioning Research, 2006)
Anecdotal and research evidence is that vertical jump performance declines over the competitive volleyball season. The purpose of this study was to evaluate whether a short period of ballistic resistance training would attenuate this loss. Fourteen collegiate women volleyball players were trained for 11 weeks with periodized traditional and ballistic resistance training. There was a 5.4% decrease (p < 0.05) in approach jump and reach height during the traditional training period (start of season to midseason), and a 5.3% increase (p < 0.05) during the ballistic training period (midseason to end of season), but values were not different from start to end of season. These changes in overall jump performance were reflective of changes in underlying neuromuscular performance variables: in particular, power output and peak velocity during loaded jump squats, countermovement jumps, and drop jumps. During the first 7 weeks of traditional heavy resistance training, it appears that the neuromuscular system is depressed, perhaps by the combination of training, game play, and skills practice precluding adequate recovery. Introduction of a novel training stimulus in the form of ballistic jump squats and reduction of heavy resistance training of the leg extensors stimulated a rebound in performance, in some cases to exceed the athlete's ability at the start of the season. Periodization of in-season training programs similar to that used in this study may provide volleyball players with good vertical jump performance for the crucial end-of-season games.